(untitled) (Research, Society and Development, 2022)
Syphilis is a communicable disease and is considered a serious public health problem. It can be acquired in the sexual act or through the mother’s placenta, thus concretizing congenital syphilis. The damage that affects the fetus is severe and even includes death. The nursing professional is present throughout the monitoring of pregnancy, playing an important role in combating the disease, through good prenatal care and health education. The objective of this research was to identify the knowledge of nurses about the preventive measures that should be taken by Primary Care in the municipality of Bragança for the prevention of syphilis in pregnant women. This is a research with a qualitative approach, of the descriptive-exploratory type. Data collection was carried out through a questionnaire containing 08 open questions, to establish an understanding of the treatment logistics and prevention measures for gestational syphilis in prenatal care, directed to the nurse coordinator of the team of each unit. Data collection was carried out in October 2019. The survey showed that syphilis still represents a serious public health problem. It is concluded that nursing plays a fundamental role in the control and prevention of syphilis, and it is also necessary to implement new public policies in Primary Health Care focused on syphilis, in order to reduce the number of cases in the country, improving quality. of life of the population.